Working with Deprived and Depraved Children in the Perspective of Symbolic Interactionism - Maciej Witold Bernasiewicz (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: By creating a framework composed of such concepts as the self, definition of the situation, meaning, joint action, making indications, and social labelling, symbolic interactionism (SI) provides us with a useful conceptual apparatus for understanding human behavior and analyzing the process of criminogeneity.   Research Aim: Similar to the way that Howard Becker has discussed the social character of deviations using excerpts of interviews that he carried out with marijuana smokers and jazz musicians, I try to show on the basis of interviews with counsellors how we can use methods of rehabilitation drawing from SI to social work and treatment of at-risk and delinquent youth. Method: These findings were based on data drawn from in-depth interviews (semi-structured) with counsellors from day care treatment centres (sociotherapists). Results: The article presents four methods of rehabilitation and social work with at-risk and delinquent youth, which were generated from collected data and from the theory of SI. Conclusion: Probation officers, social workers, counsellors, street workers, sociotherapists are professions that can use the ideas and methods presented in the article in their professional practice.